Atypical cytologic presentation of a histiocytic sarcoma in a Cavalier King Charles Spaniel dog. (July 2017) - Clarke, Lorelei L.; Kelly, Lisa S.; Garner, Bridget; Brown, Cathy A.
A Cavalier King Charles Spaniel dog was presented because of a 10-d history of progressive vomiting, inappetence, and lethargy, with mild neurologic signs. Fine-needle aspirates of splenic nodules seen on ultrasound were suggestive of a carcinoma. On autopsy, a disseminated neoplasm was present in the lung, spleen, and adrenal glands. Additionally, there was a Chiari-like malformation of the skull with corresponding syringomyelia of the cranial spinal cord. Histologically, the neoplasm was comprised of a pleomorphic population of round cells with a high mitotic rate. Cells stained positive for vimentin and CD18 and negative for cytokeratin, chromogranin A, CD3, CD20, MHC II, and CD11d, and hence the tumor was diagnosed as a histiocytic sarcoma. The cytologic presentation in this case is uncommon for this type of tumor, as was the clinical presentation.